Persepsi Guru SMA Negeri 1 Kotaagung Terhadap Literasi Digital di Masa COvid 19 - Fitra, Jaka; Ramadaniah, Dedeh; Ramadhani, Apriliana (UIN Raden Intan Lampung, 2021)
The Corona Virus Diseases 19 (COVID-19) pandemic causes uncertainty, many educational institutions are unable to carry out face-to-face learning processes due to the impact of distance restrictions. Advances in communication and information technology in the world of education, one of the supporters of educators in developing learning media, utilizes the e-learning system to increase the flexibility of learning and teaching. By using digital literacy, learning media can be easily accessed anytime and anywhere. The use of computers and smartphones proves that SMAN 1 Kotaagung (Public Senior High School 1 Kotaagung) has started using digital literacy in the teaching and learning process as well as when looking for sources of learning materials, such as text, images, and video teaching materials that are carried out by both teachers and students.